2016
DOI: 10.18632/oncotarget.13236
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of L1 cell adhesion molecule in cancer patients: A systematic review and meta-analysis

Abstract: The L1 cell adhesion molecule (L1CAM) extensively participates in nervous system development and the malignant progression of human tumours. The prognostic value of L1CAM for the survival of patients with solid tumours remains controversial. The present meta-analysis was thus performed to highlight the relationship between L1CAM expression and prognosis in cancer patients. Relevant publications were identified after searching several widely used databases, including PubMed, EMBASE and the ISI Web of Science. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 53 publications
(67 reference statements)
0
25
0
4
Order By: Relevance
“…Expression of L1CAM has been investigated in several cancer types, and is associated with poor outcome ( Fogel et al , 2003 ; Allory et al , 2005 ; Boo et al , 2007 ; Schroder et al , 2009 ; Tischler et al , 2011 ; Tsutsumi et al , 2011 ; Wang et al , 2013 ; Hua et al , 2016 ). In endometrial cancer hysterectomy samples, L1CAM has been reported to be associated with aggressive disease characteristics including loss of hormone receptors and reduced survival ( Huszar et al , 2010 ; Zeimet et al , 2013 ; Bosse et al , 2014 ; Dellinger et al , 2016 ; Geels et al , 2016 ; van der Putten et al , 2016 ; Kommoss et al , 2017 ).…”
mentioning
confidence: 99%
“…Expression of L1CAM has been investigated in several cancer types, and is associated with poor outcome ( Fogel et al , 2003 ; Allory et al , 2005 ; Boo et al , 2007 ; Schroder et al , 2009 ; Tischler et al , 2011 ; Tsutsumi et al , 2011 ; Wang et al , 2013 ; Hua et al , 2016 ). In endometrial cancer hysterectomy samples, L1CAM has been reported to be associated with aggressive disease characteristics including loss of hormone receptors and reduced survival ( Huszar et al , 2010 ; Zeimet et al , 2013 ; Bosse et al , 2014 ; Dellinger et al , 2016 ; Geels et al , 2016 ; van der Putten et al , 2016 ; Kommoss et al , 2017 ).…”
mentioning
confidence: 99%
“…In many cases, the expression level of L1CAM correlates with adverse prognosis [61]. For example, L1CAM has recently emerged as an important prognostic biomarker in endometrial carcinoma [62,63].…”
Section: L1cammentioning
confidence: 99%
“…The L1 cell adhesion molecule (L1CAM; CD171) is a 200–220 kDa membrane glycoprotein that is thought to be involved in the pathogenesis of cancers by increasing their motility, invasiveness, growth and transformation rate . Expression of L1CAM has been found to be a negative prognostic factor in numerous cancers, and therapies that target the L1CAM protein is a subject of ongoing investigations . In endometrial carcinomas, most investigators have found L1CAM expression to identify otherwise ‘low risk’ patients that are at increased risk for recurrence, to correlate with adverse factors such as deep myometrial invasion, advanced stage, nodal involvement, non‐endometrioid histology, lymphovascular invasion, high tumor grade, and distant relapses, and generally, to be a poor prognostic factor in endometrioid carcinomas .…”
Section: Clinicopathological Features Of Data Set Including Stratifimentioning
confidence: 99%